REACTION OF Crambe abyssinica TO Meloidogyne javanica AND M. incognita RACE 3 - Souza, Rafael Assis de (2019)
Several oilseed plants have been researched for biodiesel production in Brazil, and Crambe abyssinica Hochst is one of the most promising species. The effect of the phytonematodes M. incognita race 3 and Meloidogyne javanica on C. abyssinica plants was evaluated in greenhouse experiments. A randomized block design with five nematode inoculum levels (350, 700, 1400, 2800, and 5600 eggs) and ten replications was used. C. abyssinica plants without inoculation were used as controls, and the viability of the nematodes used was tested in tomato plants inoculated with 2000 eggs. The plots consisted of pots containing one plant. The number of root knots (NG), number of egg masses (NEM), and number of eggs + second-stage juveniles (NEJ2) per root system, number of J2 per 200 cm3 of soil (NJ2), and shoot dry weight (SDW) of the inoculated C. abyssinica plants were evaluated at 45 days after inoculation. The reproduction factor (RF) of the nematodes was also evaluated. The resistance of the plants to the phytonematodes was classified using the RF criterion. Crambe abyssinica plants are susceptible to the different inoculum levels of Meloidogyne javanica and M. incognita used, and the data of all nematode variables (NG, NEM, NEJ2, NJ2, and RF) were fitted by linear models.